Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1152/ajpcell.00118.2002
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic bile ducts transport water in response to absorbed glucose

Abstract: The physiological relevance of the absorption of glucose from bile by cholangiocytes remains unclear. The aim of this study was to test the hypothesis that absorbed glucose drives aquaporin (AQP)-mediated water transport by biliary epithelia and is thus involved in ductal bile formation. Glucose absorption and water transport by biliary epithelia were studied in vitro by microperfusing intrahepatic bile duct units (IBDUs) isolated from rat liver. In a separate set of in vivo experiments, bile flow and absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…It is tempting to speculate that this type of mechanism might operate physiologically not only in the crypts of the small intestine, but also in the intrahepatic bile ducts and in distal portions of the nephron and renal calices. Supporting this assumption, glucose absorption from the bile by cholangiocytes was already reported and proposed to be an important factor to drive water reabsorption (Guzelian and Boyer 1974;Masyuk et al 2002). Indeed, rather low glucose concentrations ranging from 50 to 300 mg/l were measured in rat bile (Guzelian and Boyer 1974).…”
Section: Discussionmentioning
confidence: 73%
“…It is tempting to speculate that this type of mechanism might operate physiologically not only in the crypts of the small intestine, but also in the intrahepatic bile ducts and in distal portions of the nephron and renal calices. Supporting this assumption, glucose absorption from the bile by cholangiocytes was already reported and proposed to be an important factor to drive water reabsorption (Guzelian and Boyer 1974;Masyuk et al 2002). Indeed, rather low glucose concentrations ranging from 50 to 300 mg/l were measured in rat bile (Guzelian and Boyer 1974).…”
Section: Discussionmentioning
confidence: 73%
“…In rat, it has been shown that glucose enters the bile passively from hepatocytes and is reabsorbed in bile ducts by phlorizin-inhibitable Na + -D-glucose cotransport [9,17]. Employing an ex vivo study with bile duct units isolated from rat liver, it has been shown that the secondary active reabsorption of glucose in the bile ducts provides the osmotic driving force for water reabsorption via aquaporins [31]. This mechanism may explain the observation that the bile flow decreases in diabetic rats [8] and may contribute to cholestasis during diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The protein product of Clic4, a mitochondrial chloride channel protein, has been implicated in apoptotic response to DNA damage (FernandezSalas et al 2002). The water channel protein aquaporin 2 apparently is not expressed in rat liver (Umenishi et al 1996, Huebert et al 2002, but has not been studied in mice; it may have a role in glucose-driven water transport in liver (Masyuk et al 2002).…”
Section: Discussionmentioning
confidence: 99%